As orações existenciais em inglês e português brasileiro: um estudo baseado em corpus - Kicila Ferreguetti de Oliveira (2014)
This thesis draws on Systemic Functional Linguistics (SFL) and presents a study of existential clauses retrieved from a parallel corpus of originals and their translations, aimed at identifying a prototypical configuration for the existential clauses in the originals in Englishand examining how they were translated into Brazilian Portuguese. Data were retrieved from Klapt!, an English/Brazilian-Portuguese bidirectional parallel and comparable corpus, compiled with texts from eight different text types (Research Article, Political Speech, Popular Science, Fiction, Instructions Manual, Tourism Leaflet, Review and EducationalWebsite). The analysis focused on the English/Brazilian-Portuguese direction (originals in English and their translations into brazilian-Portuguese) and was carried out in two mainsteps. First, WordSmith Tools (SCOTT, 2007) was used to query the corpus for occurrences of existential clauses that were extracted and annotated using UAM Corpus Tool(ODONNELL, 2008) according to the types of existential Processes, Existents and Circumstances (Halliday; Matthiessen, 2004) observed in each of them. The data were subsequently analyzed from SFLs trinocular perspective in order to obtain a prototypicalconfiguration for the existential clauses in the English subcorpus as a whole and per text type,together with the function they realize in each text type. The second step comprised the analysis and annotation of the translated existential clauses. This was done through the alignment of original and translated texts in order to identify and retrieve translationequivalents. The retrieved translations were annotated according ow the existentialProcesses were translated into Brazilian Portuguese based on the concepts of textual equivalence, formal correspondence (CATFORD, 1965) and shift (CATFORD, 1965; MATTHIESSEN, 2001). Finally, a multivariate statistic analysis was carried out in order toidentify possible associations among the text types regarding the construal and translation of existential meanings. Results showed that the most frequent configuration for existential clauses in the English subcorpus is existential Process (realized by the verb to be in a there + verb to be construction), followed by Existent (realized by Things of the abstraction/semiotic type). This configuration was the most frequent in seven out of the eight analyzed text types.Other possible configurations were also observed, which were considered prototypical and varied according to the function realized by the existential clauses in each of the text types.The analysis of the translated existential clauses, in turn, revealed that, in 76,2% of the occurrences, the existential Processes in English were translated into existential Processes in Brazilian Portuguese, with this percentage varying considerably among text types. Shifts wereobserved in 21,9% of the occurrences and varied among text types as well. The most frequent types of shifts were shifts from existential Processes in English to relational and material Processes in Brazilian- Portuguese